Optimising the exchange: a review of baton passing strategies in 4x100 m relay - Rosculet, I.; Tomescu, G.; Dulceata, V. (Science, Movement & Health, 2025)
The relay race, particularly the 4x100m event, presents unique challenges that integrate both physical capabilities and technical skills, especially during baton exchanges in high-speed conditions. This synthesis reviews three studies aimed at quantifying performance factors critical to successful baton handoffs and overall race efficiency. The first part of the paper introduces mathematical equations to evaluate the technical aspects of baton exchanges, proposing a framework that allows coaches to identify weaknesses and predict team performance without complex procedures. Utilising data from elite and non-elite teams, this approach emphasises the potential for improving relay outcomes through targeted analysis.